Key to High School English Grammar and Composition Regular and Multi-color Edition - Martin, Wren; P.C. Wren; H. Martin (India S. Chand & Company Ltd., 2006)
Provides solutions to exercises, aiding students in understanding grammar concepts. it includes paragraph writing, story writing, letter writing, precis writing, essay writing, autobiography, dialogue writing, paraphrasing, exercises with answers & expansions.
Answer key to exercises in "High School English Grammar and Composition"
Keywords: Wren Martin - Key to High School English Grammar and Composition